2003
DOI: 10.4049/jimmunol.170.7.3603
|View full text |Cite
|
Sign up to set email alerts
|

Role of MHC Class I in Immune Surveillance of Mitochondrial DNA Integrity

Abstract: Mitochondrial DNA is subject to increased rates of mutations due to its proximity to the source of reactive oxygen species. Here we show that increased MHC class I (MHC I) expression serves to alert the immune system to cells with mitochondrial mutations. MHC I is overexpressed in fibroblasts with mitochondrial dysfunction from patients with mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes and in lymphocytes from purine nucleoside phosphorylase-deficient immune-deficient mice with mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…These events, in turn, lead to the induction of regulatory T cells (Treg), downmodulation of antigen-presenting cells, with concomitant loss of T-cell effector function68 or loss of functional major histocompatibility class I receptors 69…”
Section: Concept 5: Tumour Microenvironmentmentioning
confidence: 99%
“…These events, in turn, lead to the induction of regulatory T cells (Treg), downmodulation of antigen-presenting cells, with concomitant loss of T-cell effector function68 or loss of functional major histocompatibility class I receptors 69…”
Section: Concept 5: Tumour Microenvironmentmentioning
confidence: 99%
“…Mutations in mtDNA associated with infectious or autoimmune disease processes can be recognized by CD4 + and CD8 + T lymphocytes, suggesting a surveillance role of the immune system in eliminating cells harboring mitochondrial defects [35]. Furthermore, a unique somatic mutation in 'cytochrome b' has been shown to be recognized by melanoma-specific CD4 + T cells from one patient [36].…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, it was demonstrated that lymphocytes from PNP-deficient mice harbored mtDNA deletions various sizes and also overexpressed MHC class I. These findings, and the observation that MHC I-deficient mice accumulated mtDNA deletions, suggested that cells with impaired mtDNA integrity may also be eliminated by cytotoxic T cell killing (Gu et al, 2003). Contrary to PNP deficiency, SCID due to adenosine deaminase (ADA) deficiency is not a mitochondrial disorder as accumulated dAdo is efficiently phosphorylated in the cytosol by CK and ADK in lymphocytes (Hershfield et al, 1982;Arpaia et al, 2000).…”
Section: Purine Nucleoside Phosphorylase (Pnp) Deficiencymentioning
confidence: 96%
“…However, mitochondrial dNTP metabolism may differ between humans and mice; for example, mice with targeted deletion of both TP and uridine phosphorylase did not express mtDNA alterations or pathological changes in muscle, although they had elevated plasma dThd and brain lesions (Haraguchi et al, 2002). Also, mice with inactivated ANT1 or PNP could serve as model systems for mtDNA instability (Esposito et al, 1999: Gu et al, 2003.…”
Section: The Intervention Of Mitochondrial Deoxyribonucleotide Metabomentioning
confidence: 97%